(untitled) (Revista de Ciências Agroveterinárias, 2009)
The Normative Instruction 51/2002 of the MAPA (NI 51) defined technical regulations for the production, identity and quality of several types of milk. Total Bacterial Count (TBC) and Somatic Cell Count (SCC) are important parameters to evaluate, respectively, the milk microbiological quality and the mammary gland health, being part of a group of quality attributes that include composition, sensorial aspects and absence of drugs and chemical residues. It is important to evaluate the influence of dairy farmer’s profile, milking procedures and the kind of equipment used on the adaptation of dairy farms to the limits established for TBC and SCC in the NI 51. In order to perform these evaluations, a questionnaire was answered for 166 dairy farmers in the middle-west and high Itajai valley of Santa Catarina State, southern Brazil, from April to September of 2006. The effects of farmer instruction level, amount of milk production in the farm, milking procedures, equipments and knowledge about the norms of milk quality on the farmer’s adaptation to the NI 51 were assessed. On the average, the percentage of no-conformity to NI 51 was 11.3% for SCC and 73.1% for TBC. Farms that produced more than 200 liters per day presented greater conformity to NI 51 for TBC, but not for SCC. Farmers with larger instruction level also had better results for TBC, but not for SCC. The farmer satisfaction degree with the activity and the milk importance as the main economic activity in the farm did not influence the adaptation to the legislation. Farms with manual milking had better results for TBC. Preparation of the udder before milking affected the results only for TBC, with better results for farmers that use pre-dipping. Milk cooling in bulk tanks or in milk cans did not affect milk quality. The milking and milk cooling procedures did not affect the adaptation to NI 51 for SCC. Most farmers had little knowledge about the norms of milk quality and this knowledge didn’t affect milk quality. The majority of milk farms on the researched areas were adapted to the established by NI 51 for SCC, but not for TBC. The use of correct hygiene techniques improved the adaptation to the legislation. The same did not happen with the simple acquisition of equipments (milking equipment and bulk tank).